2006
DOI: 10.1007/s00134-006-0376-2
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of erythrocyte concentrates produces a variable increment on cerebral oxygenation in patients with severe traumatic brain injury

Abstract: Erythrocyte transfusion is associated with a variable and prolonged increment of cerebral tissue oxygenation in anemic patients with severe traumatic brain injury. Low baseline PtiO(2) levels (<15mmHg) could define those patients who benefit the most from erythrocyte transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 24 publications
1
64
0
6
Order By: Relevance
“…PbtO2 monitoring is almost exclusively used in combination with other cerebral non-invasive and invasive monitoring modalities, in particular intracranial pressure [ICP] monitoring [4, 6, 17, 22, 24, 26, 32, 33, 50, 51, 53, 55, 72, 81, 88 202, 91, 130, 176, 187, 203, 206, 219-223], cerebral perfusion pressure (CPP) monitoring [3,4,10,25,178,187,198,[224][225][226], jugular venous saturation (JvDO2) monitoring [184,190,206,227,228] 88 202, 178, 237], regional cerebral blood flow measurements (rCBF) [47,[240][241][242], near infrared spectroscopy (NIRS) [15,123,179,190,243], intracranial temperature measurements [9,97,99,141], oxygen-15 positron emission tomography (15O-PET) [230], continuous surface electroencephalogram [94], and cortical spreading depolarizations (CSD) monitoring using subdural electrocorticography (ECoG) strip electrodes [244].…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…PbtO2 monitoring is almost exclusively used in combination with other cerebral non-invasive and invasive monitoring modalities, in particular intracranial pressure [ICP] monitoring [4, 6, 17, 22, 24, 26, 32, 33, 50, 51, 53, 55, 72, 81, 88 202, 91, 130, 176, 187, 203, 206, 219-223], cerebral perfusion pressure (CPP) monitoring [3,4,10,25,178,187,198,[224][225][226], jugular venous saturation (JvDO2) monitoring [184,190,206,227,228] 88 202, 178, 237], regional cerebral blood flow measurements (rCBF) [47,[240][241][242], near infrared spectroscopy (NIRS) [15,123,179,190,243], intracranial temperature measurements [9,97,99,141], oxygen-15 positron emission tomography (15O-PET) [230], continuous surface electroencephalogram [94], and cortical spreading depolarizations (CSD) monitoring using subdural electrocorticography (ECoG) strip electrodes [244].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…They conclude that Erythrocyte transfusion is associated with a variable and prolonged increment of cerebral tissue oxygenation in anemic patients with severe traumatic brain injury. Low baseline pbtO2 levels (<15mmHg) could define those patients who benefit the most from erythrocyte transfusion [3]. Another severe TBI series demonstrated that 57% of patients had a pbtO2 increase, whereas in 43% of patients, pbtO2 either did not change or decreased.…”
Section: Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…10 Despite that, universal blood transfusion triggers continue to be controversial, and there is evidence to suggest that "dosing" blood by unit(s) as opposed to absolute hematocrit targets may be more prudent in the context of brain tissue oxygenation. [11][12][13] The age of the transfused blood may also be an important consideration, with more favorable cerebral oxygenation responses seen following transfusions of blood stored for fewer than 19 days. 11 Therapy directed at correcting hypovolemic shock includes prompt volume expansion with crystalloid solutions, followed by administration of blood products as per established trauma guidelines.…”
mentioning
confidence: 99%
“…Similarly, the short-term ICPreducing effect of barbiturate therapy may turn into adverse effects when barbiturates are given for many days or in high concentrations due to negative pulmonary effects with secrete stagnation, electrolyte disturbances, and cardio-inhibitory effects (10). Acceptance of low haemoglobin concentrations may be justified by avoiding negative transfusion effects and the possibly beneficial effects of a subnormal viscosity, but low haemoglobin concentration may also mean a suboptimal oxygen-delivery capacity, and difficulties in maintaining normovolaemia and normal blood pressure (11,12). Vasoconstrictor therapy (e.g.…”
mentioning
confidence: 99%